Microwave Induced Stereoselective Synthesis of O–Vinyl Oximes using Acetylenic Esters as Efficient Michael Acceptors - Mishra A.; Singh S.; Quraishi M.A.; Srivastava V. (My University, 2025)
A new and convenient stereoselective synthesis of O–vinyl oximes involving Michael addition of N–hydroxysuccinimidyl derivatives to dialkyl acetylenedicarboxylates under conventional and microwave irradiation methods is described. Michael acceptors diethyl and dimethyl acetylenedicarboxylates yielded a mixture of syn-(E) and anti-(Z) isomers by conventional method. However, microwave irradiation stereoselectively yielded both isomers at different experimental parameters. The role of lone pairs of oxygen in sp3-hybridized state in controlling the conformational preferences about N−O bond has also been demonstrated. The structures and stereochemistry of the adducts were established through FT-IR, 1H, 13C NMR spectroscopy and X–ray crystallography. © 2018 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim